2017
DOI: 10.17509/ijal.v7i1.6863
|View full text |Cite
|
Sign up to set email alerts
|

Translators’ Censorship in English-Indonesian Translation of Donald Duck Comics

Abstract: Not all aspects of Western culture, reflected in the language used in Walt Disney's Donald Duck comics, are acceptable in Indonesia. So, in translating the comics, the translators have to manipulate the text for it to be acceptable by the target readers and parents. This research aims at finding out censorship through the translation techniques used by the translators in translating the English humorous texts in the Walt Disney's Donald Duck comics into Indonesian and the reasons underlying the translators' ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…literary texts, according to Vieira and Alonso (2020), could not be translated by using machine translations since literary texts needed a high level of sensitivity in translating them. A similar example was given by Yuliasri (2017) in the translation of comics from English into Indonesian through reducing inappropriate words, i.e. sarcasm, and carefully selecting appropriate terminologies acceptable for children and teenagers as the biggest segment of readers in Indonesia.…”
Section: Post-editing Academic Texts In Different Topicsmentioning
confidence: 93%
“…literary texts, according to Vieira and Alonso (2020), could not be translated by using machine translations since literary texts needed a high level of sensitivity in translating them. A similar example was given by Yuliasri (2017) in the translation of comics from English into Indonesian through reducing inappropriate words, i.e. sarcasm, and carefully selecting appropriate terminologies acceptable for children and teenagers as the biggest segment of readers in Indonesia.…”
Section: Post-editing Academic Texts In Different Topicsmentioning
confidence: 93%
“…The study of translation as a product has been carried out by many researchers in various types of text and fields, such as medicine (Silalahi, 2009), literary (Siregar, 2015), Holly Koran (Anshori, 2016), censorship (Yuliasri, 2017), translation training (Karnedi, 2015), Javanese translation from Bidāyah al-hidāyah written by al-Ghazāli (Anis & Saddhono, 2016), and use of Arabic-Javanese books in Islamic education (Munip, 2016). In fact, alJailānī's hagiography has been studied from a political perspective (Saerozi, 2007;Sahri, 2011) instead of its translation; hence, this study is focused on describing the technique, method, and ideology of translation adopted by the translator.…”
Section: Technique Method and Ideology Of Translationmentioning
confidence: 99%
“…In the Indonesian context, our research revealed that the big publishers -including the publisher of HPSSdevelop guidelines for translators to ensure that cultural norms are adhered to and taboos are not violated. Yuliasri's study of the Indonesian translation of Donald Duck comics also reveals how the translators were expected to manipulate the text in order for it to be acceptable to readers and parents (Yuliasri, 2017).…”
Section: Translation Techniquesmentioning
confidence: 99%